Pharmaceutical care in the state of Ceará, Brazil: socioeconomic and demographic profile of patients with chagas disease attended in a referral center - Eduardo Menezes Viana, Carlos; Arrais Rocha, Eduardo; Rosa Pinto Quidute, Ana; Carla da Costa, Alanna; Coelho Andrade, Monica; Mesquita Lacerda, Julieth; Igor de Oliveira Jaco , Jose; Oliveira, Maria de Fátima (Revista de Patologia Tropical / Journal of Tropical Pathology, 2021)
The Pharmaceutical Care Service of the Chagas Disease Research Laboratory (LPDC), in the State of Ceará, Brazil, treats patients with Chagas disease (CD), characterized as a chronic, neglected disease that requires full patient follow-up. Objective: determine the socioeconomic and demographic profile of patients with CD treated at the LPDC. A descriptive cross-sectional study was carried out, in which 507 patients were treated from January 2007 to May 2016. The variables collected were gender, age, place of birth, schooling, family income, type of health care, occupation, living conditions and habits. The profile of Trypanosoma cruzi infected individuals consisted of 51.1% males; mean age of 50.4 years; 26.6% were small farmers; 48.7% had not finished elementary school; 36.9% had a family income of one minimum wage; 77.7% did not have private health insurance and most of them came from rural areas. Regarding habits, 66.5% were nonsmokers and 70.0% were sedentary. Additionally, an improvement was noted in housing conditions, with most patients moving from wattle and daub huts, which were their first homes, to brick houses. We conclude that the analysis of the socioeconomic and demographic profile of patients treated at the LPDC showed that most of them come from a low socioeconomic population, where the demand for treatment has been occurring at a later age, further reinforcing the importance of the follow-up provided by the LPDC. KEY WORDS: Chagas disease; health services research; health profile; pharmaceutical care.